Quantitative and qualitative study of buffalo oocytes recovered by different oocyte harvesting techniques - CHAUDHARI, C F; DERASHRI, H J; CHAUDHARY, SANDHYA S; PURI, GOPAL (The Indian Journal of Animal Sciences, 2014)
Present study was undertaken to assess the comparative efficacy of oocyte harvesting techniques, viz. aspiration and slicing methods on oocyte retrieval, recovery rate and quality of oocytes recovered in buffalo ovaries obtained from local slaughterhouse. Oocyte retrieval rate was significantly higher in slicing (67.75%) than aspiration (41.58%) technique. The oocyte recovery rate from ovaries by slicing (3.05 ± 0.24) was significantly higher than those by aspiration (1.76 ± 0.13) technique. The mean number of oocytes/ovary of grade I (0.93 ± 0.03) was significantly higher than grade II (0.55 ± 0.04) and grade III (0.34 ± 0.05) in aspiration technique. The reverse trend was observed in slicing technique, where the mean number of oocytes/ovary of grade III (1.32 ± 0.05) was significantly higher than grade II (1.07 ± 0.06) and grade I (0.81 ± 0.06). In both the techniques of oocyte collection, viz. aspiration and slicing the percentage of BCB+ oocytes (68.39% and 53.51%, respectively) were significantly higher than BCB– oocytes (31.61% and 46.49%, respectively). Overall higher numbers of oocytes were in BCB+ (60.29%) than BCB– (39.71%). In conclusion, quantitatively slicing was better over aspiration, while qualitatively aspiration technique was found to be superior over slicing technique.